PENJADWALAN PROYEK PEMBUATAN ROLLING MACHINE MENGGUNAKAN METODE JALUR KRITIS - Ratih Wulandari (Asosiasi Dosen Muda Indonesia, 2023)
Scheduling is very important in the basis of project planning so that it can run smoothly and can be completed on time. Before the project is carried out, it is necessary to have a project management stage which includes the planning stage, the scheduling stage and the coordination of these stages. Estimation of completion time for the production of rolling machine projects scheduled by PT. X is 36 days, the actual time in working on the rolling machine project is 32 days, then the estimated time for completing the iron rolling machine project using Microsoft Project is 27 days. The sequence of work processes using the critical path starts with number 1.1-1.2-2.1-4.1-4.2-4.3-4.7-4.8-6.1-6.2-6.3-7.1-7.2-7.3-7.4-7.5-7.6-7.7-7.8-7.9-7.10-8.1-8.2.